2020
DOI: 10.1002/agg2.20123
|View full text |Cite
|
Sign up to set email alerts
|

Coal char affects soil pH to reduce ammonia volatilization from sandy loam soil

Abstract: Ammonia (NH 3) volatilization loss adversely affects N availability in soil-plant systems, reduces crop yield, and negatively impacts environment. Char (coal combustion residue), which contains up to 293 g kg −1 total C by weight, has been shown to reduce NH 3 volatilization due to its considerably high surface area and cation exchange capacity. The NH 3 loss can be greatly affected by a shift in soil pH or urea hydrolysis. A 21-d laboratory study was conducted to evaluate the effects of char on soil pH, N tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…A significant decrease in soil pH with addition of char up to 13.4 Mg C ha −1 compared with the control could be due to soil dilution effect with char (Thomas, 1996). Similar results were observed in the incubation study that reported reduction in soil pH with the char applied at 13.4 Mg C ha −1 in urea‐fertilized sandy loam compared with no char treatments (Panday et al., 2020b). Lai et al.…”
Section: Discussionsupporting
confidence: 86%
“…A significant decrease in soil pH with addition of char up to 13.4 Mg C ha −1 compared with the control could be due to soil dilution effect with char (Thomas, 1996). Similar results were observed in the incubation study that reported reduction in soil pH with the char applied at 13.4 Mg C ha −1 in urea‐fertilized sandy loam compared with no char treatments (Panday et al., 2020b). Lai et al.…”
Section: Discussionsupporting
confidence: 86%
“…The relatively high C content among different types of coal combustion residues makes this char also valuable for efforts to restore soil C storage in degraded soils (Blanco‐Canqui et al., 2020). However, to the best of our knowledge, data on this char material to improve agricultural soil are limited to four published studies (Blanco‐Canqui et al., 2020; Panday, Mikha, Collins, et al., 2020; Panday, Mikha, & Maharjan, 2020; Panday et al., 2021). From a 30‐d column experiment Panday, Mikha, Collins, et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many positives of urea fertilizer, it is well reported that urea is highly susceptible to NH 3 volatilization losses when left on the soil surface (Goos & Guertal, 2019; Pan et al., 2016; Rochette et al., 2013). These NH 3 volatilization losses affect crop yields, fertilizer N use efficiency, environmental and health issues, and indirectly N 2 O emissions (Panday et al., 2020). The magnitude of NH 3 volatilization is greatly affected by soil pH, soil texture, and environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of NH 3 volatilization is greatly affected by soil pH, soil texture, and environmental conditions. Ammonia gas is preferentially formed as pH increases into the alkaline range, where added urea dissolves, hydrolyzes to form NH 4 or NH 3 , and increases pH due to the nature of the chemical reaction (Panday et al., 2020). High pH alkaline calcareous and loamy agricultural soils in the western United States (e.g., Idaho) can be more conducive to NH 3 volatilization (Dari, Rogers, & Walsh, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation